Investigating the Phenomenological Scientific Methodology in the Comparative Study of Religion: An Islamic Perspective - Mohamed Shafeen, Mohamed Ashath; Shehu, Fatmir (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
This paper aims to investigate the phenomenological scientific methodology in the study of religion, to ascertain its origin, development, and application from an Islamic perspective. Its goal is to identify the methods used in the study of religion by phenomenologists and then analyse them in the light of Islam, its sources, and the writings of selected Muslim scholars. The study employs both descriptive and analytical methods. The focus of discussion is on (1) the phenomenology of religion, its genesis and meaning; (2) the key characteristics of phenomenological scientific methodology in the study of religion; and (3) analyzing its two key concepts, i.e., the epoché and the eidetic vision from the Islamic point of view. It is argued that studying phenomenological techniques from an Islamic perspective enables researchers to recognise both the negative and positive aspects of the methodology and to understand this area of study more effectively when conducting religious studies. This paper concludes that, although there are strong refutations against the phenomenological scientific methodology of comparative religious studies from an Islamic perspective, it also has an acceptable level.